2013
DOI: 10.5604/15093492.1058409
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral lesions of the knee reconstructed with mesenchymal stem cells – results.

Abstract: mó rek szpi ku. Material i metody. Ma te riał kli nicz ny sta no wi ło 46 pa cjen tów z ubyt ka mi chrzęst no -kost ny mi o ró żnej etiolo gii, po twier dzo ny mi w MRI, w dwóch gru pach: 21 cho rych za opa trzo nych z uży ciem kon cen tra tu ko mó rek szpiku i 25 cho rych le czo nych za po mo cą ko mó rek me zen chy mal nych uzy ska nych z krwi ob wo do wej. Oce nę przepro wa dzo no po 6 mie sią cach, 1 ro ku i 5 lat po re kon struk cji ubyt ku na pod sta wie skal: KO OS, Ly shol ma i VAS.Wy ni ki. Au to rzy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 12 publications
2
89
0
Order By: Relevance
“…(BMAC, bone marrow aspirate concentrate.) [15][16][17][18] However, other studies have reported using volumes as low as 30 mL 19,20 and as high as 120 mL. 21 In the present Technical Note, 60 mL of BMAC was aspirated and later processed.…”
Section: Application Of Bmacmentioning
confidence: 89%
“…(BMAC, bone marrow aspirate concentrate.) [15][16][17][18] However, other studies have reported using volumes as low as 30 mL 19,20 and as high as 120 mL. 21 In the present Technical Note, 60 mL of BMAC was aspirated and later processed.…”
Section: Application Of Bmacmentioning
confidence: 89%
“…The ultimate autologous stem cell option is of course UC blood and tissues, due to ease of collection, storage, costs, safety, and availability, but there have as yet not been any autologous uses in OA employing that source [35]. The only clinical comparative study between stem cell types in cartilage regeneration is the study of Skowroński and Rutka [36] showing superior results for PBSC versus BM. The possibility of using autologous PBSCs obtained by leukapheresis after hG-CSF stimulation was first introduced by Saw et al [13,14,16] who treated chondral knee lesions with subchondral drilling and five postoperative IA injections of PBSCs and HA, reporting no adverse reactions and positive histological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Another method to isolate MSCs is through a bedside cell concentration device that yields a bone marrow concentrate (BMC) specimen [1926]. One advantage of such a device is the quick centrifugation step used to generate the BMC, which bypasses the time-consuming step of cell culture and expansion and enables immediate administration to the patient that may translate to clinical significance.…”
Section: Introductionmentioning
confidence: 99%